In Vitro Inhibitory Activity of the α-Glucosidase Enzyme from Eucheuma cottonii Macroalgae Extract - Kurnia, Dewi; Zakiyah, Farah; Budiana, Wempi; Andriansyah, Ivan (Jurnal Kimia Riset, 2025)
Diabetes mellitus is a metabolic disorder caused by damage to the pancreas, insulin resistance, or other factors. α-glucosidase inhibitors are compounds that can prevent the breakdown of complex carbohydrates into glucose, so α-glucosidase inhibitors have the potential to be used as diabetes drugs. One of the natural marine ingredients that has the potential to act as an antidiabetic is the macroalgae Eucheuma cottoniii. This research aims to determine the potential of Eucheuma cottoniii extract in inhibiting the activity of the α-glucosidase enzyme extract using an in vitro approach. Eucheuma cottoniii was extracted by a multistage maceration method used n-hexane, ethyl acetate and 70% ethanol as solvents. Extracts were characterized by the TLC method. The α-glucosidase inhibitory activity was tested in vitro used a microplate reader at 405 nm. TLC analysis results showed that the extract of Eucheuma cottonii contained flavonoid, phenol, alkaloid, steroids, and terpenoid. The α-glucosidase enzyme inhibition activity test showed that the IC50 values of the n-hexane, ethyl acetate and 70% ethanol extracts were 567.84; 174.32 and 99.57 μg/mL, while the IC50 of acarbose as a comparison was 64.41 μg/mL. It can be concluded that Eucheuma cottoniii extract with 70% ethanol has strong α-glucosidase enzyme inhibitory activity, so it has the potential to be developed as an alternative in antidiabetic treatment.